2020
DOI: 10.3390/polym12020366
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Antioxidant Properties of Cassava Starch–Carboxymethyl Cellulose Incorporated with Quercetin and TBHQ as Active Food Packaging

Abstract: Antioxidant integration has been advocated for in polymer films, to exert their antioxidative effects in active packaging. In this study, the new antioxidant food packaging made from cassava starch–carboxymethyl cellulose (CMC), which is biodegradable, edible and inexpensive, was developed. Their properties were determined and applied in food models for application. Antioxidants (quercetin and tertiary butylhydroquinone (TBHQ)) were added at various concentrations into cassava starch–carboxymethyl cellulose (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…These results confirm that a higher antioxidant capacity was obtained for additive films because of the pigments in the matrix [2]. Tongdeesoontorn et al [41] reported the addition of antioxidants (quercetin and tertiary butylhydroquinone (TBHQ)) at various concentrations into cassava starch-carboxymethyl cellulose (CMC) (7:3 w/w) films containing glycerol (30% w/w starch-CMC) as a plasticizer. The result showed that antioxidants improved tensile strength but reduced elongation at break of the cassava starch-CMC film.…”
Section: Mechanical Propertiessupporting
confidence: 54%
“…These results confirm that a higher antioxidant capacity was obtained for additive films because of the pigments in the matrix [2]. Tongdeesoontorn et al [41] reported the addition of antioxidants (quercetin and tertiary butylhydroquinone (TBHQ)) at various concentrations into cassava starch-carboxymethyl cellulose (CMC) (7:3 w/w) films containing glycerol (30% w/w starch-CMC) as a plasticizer. The result showed that antioxidants improved tensile strength but reduced elongation at break of the cassava starch-CMC film.…”
Section: Mechanical Propertiessupporting
confidence: 54%
“…The process of casting the cassava starch/gelatin film was adapted from methods published by Tongdeesoontorn et al [ 10 , 27 ]. The film-forming solution of cassava starch (7 g) and gelatin (3 g) in distilled water (200 mL) was prepared with different quercetin and TBHQ contents (0, 20, 50, and 100 mg) ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…As food additives, antioxidants are commonly used to improve the oxidation stability of lipids and to extend the shelf life, especially for fatty products and foods sensitive to O 2 . Owing to their chemical stability, low cost, and availability, synthetic antioxidants such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and tertiary butylhydroquinone (TBHQ) are widely used in the food industry [ 10 ]. In the United States, BHA and BHT are approved for human consumption with maximum concentration allowed at 200 mg/kg in fat [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the worldwide consumption of plastic has been increasing, causing serious environmental problems due to its inability to biodegrade [ 1 , 2 , 3 , 4 , 5 ]. For this reason, the use of renewable resources is being explored, which can reduce the problems of waste disposal, and the development of films with biodegradable materials is a promising alternative that offers low cost, degradability, edibility, and properties similar to common plastics [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%